PENGARUH INTENSITAS MODAL, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Cahyo, Meichelle Kurniawan; Napisah, Napisah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
Tax avoidance is a way of tax saving action that is still within the corridors of legislation and a series of tax planning activities. Tax avoidance can be said as reducing taxes by following existing regulations. The problem of tax avoidance is quite complicated, on the one hand, tax avoidance is permissible and on the other hand, tax avoidance is not desirable.This research aims to determine the effect of Capital Intensity, Sales Growth, Company Size, and Corporate Governance on Tax Avoidance. The tax system in Indonesia uses a self-assessment system, which is an authority or trust given by the government to calculate and report its own taxes. The research population is transportation and logistic companies that listed on the Indonesia Stock Exchange for the period of 2015-2021 with a total 30 companies and after following the sample criteria, there are 14 companies. The sampling technique is using purposive sampling technique. Data analysis technique in this research is Panel Data Regression that using Microsoft Excel and EVIEWS version 12. Data analysis used are Descriptive Statistical Analysis, Panel Data Regression Model Estimation, Classical Assumption Test, And Hypothesis Test. Based on the results of the Coefficient of Determination Test (R2), the influence given by the independent variable in this research was 29% and the remaining 71% was influenced by other variables not included in this research. F-test results, Capital Intensity, Sales Growth, Company Size, and Corporate Governance have a simultaneous effect on Tax Avoidance. While of the results of the t-test show that Capital Intensity has an effect on Tax Avoidance, Sales Growth has an effect on Tax Avoidance, Company Size has an effect on Tax Avoidance. Corporate Governance has an effect on Tax Avoidance.